Biorefineries in Sweden: Perspectives on the opportunities, challenges and future. (11th August 2016) - Palgan, Yuliya Voytenko; McCormick, Kes
Abstract: A growing political interest in the development of biorefineries is being shaped by climate change and a need to develop economically viable substitutes (i.e., fuels, products and chemicals) to those produced in traditional oil refineries. The pulp and paper industry in Sweden has been stagnating and it is therefore potentially promising to integrate biorefining into its activities as one way of diversifying its business. Sweden has good prerequisites for a transition to a bioeconomy due to its natural geographic conditions, industry, and infrastructure. It has developed a bioeconomy strategy and piloted several biorefinery projects. At the same time, the deployment of biorefineries has been slow, and they have not reached commercial scale. The aim of this paper is to provide an overview of the current and future development of biorefineries in the context of the emerging bioeconomy in Sweden. It is based on a literature review, policy analysis, and ten interviews with bioeconomy experts. It maps key political and legal aspects, economic and raw material aspects, social and cognitive aspects, and technology and infrastructure aspects that facilitate and hinder the development and deployment of biorefineries in Sweden. This paper identifies four action points important to the development of biorefineries and the bioeconomy: (i) commitments – establish targets and policies that drive the transition; (ii) contradictions – improve alignment on visions, goals, and activities; (iii) capacity – build up infrastructure and competences to harness the potential; and (iv) collaboration – develop cooperation across sectors and between actors. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd